Analysis of the Listeria monocytogenes Population Structure among Isolates from 1931 to 2015 in Australia - Jennison, Amy V.; Masson, Jesse J.; Fang, Ning-Xia; Graham, Rikki M.; Bradbury, Mark I.; Fegan, Narelle; Gobius, Kari S.; Graham, Trudy M.; Guglielmino, Christine J.; Brown, Janelle L.; Fox, Edward M. (Frontiers in Microbiology, 2017)
Listeriosis remains among the most important bacterial illnesses, with a high associated mortality rate. Efforts to control listeriosis require detailed knowledge of the epidemiology of the disease itself, and its etiological bacterium, Listeria monocytogenes. In this study we provide an in-depth analysis of the epidemiology of 224 L. monocytogenes isolates from Australian clinical and non-clinical sources. Non-human sources included meat, dairy, seafood, fruit, and vegetables, along with animal and environmental isolates. Serotyping, Multi-Locus Sequence Typing (MLST), and analysis of inlA gene sequence were performed. Serogroups IIA, IIB and IVB comprised 94% of all isolates, with IVB the most common serogroup among clinical isolates. Serogroup IIA was the most common among dairy and meat isolates. Lineage I isolates were most common among clinical isolates, and 52% of clinical isolates belonged to ST1. Overall 39 STs were identified, with ST1 and ST3 containing the largest numbers of L. monocytogenes isolates. These STs comprised 40% of the total isolates (n=90), and both harboured isolates from clinical and non-clinical sources. ST204 was the third most common ST. The high prevalence of this group among L. monocytogenes populations has not been reported outside Australia. Twenty-seven percent of the STs identified contained exclusively clinical isolates. Analysis of the virulence protein InlA identified a truncated form of the protein among isolates from ST121 and ST325. The ST325 group contained a previously unreported novel mutation leading to production of a 93 amino acid protein. This study provides insights in the population structure of L. monocytogenes isolated in Australia, which will contribute to public health knowledge relating to this important human pathogen.